Beastly birds and bats. - Huggins-Cooper, Lynn. (Mankato, Minn : QEB pub, 2008)
"Describes unusual species of birds and their unique features and behaviors that help them adapt to their habitats"--Provided by publisher.
Includes index.
Keywords: Birds --Juvenile literature; Birds --Behavior --Juvenile literature